Influence of Ethanol Concentration and Template Ion Exchange Agent on Template Recycling in Mobil Crystalline Material 41 (MCM-41) Synthesis - Lai, Jia Yen; Ngu, Lock Hei; Twaiq, Farouq (ASEAN Journal of Chemical Engineering, 2019)
Recycling of surfactant template for several subsequent MCM-41 synthesis is necessary to reduce substantial synthesis solution disposal. In MCM-41 synthesis, ethanol concentration and template ion exchange agent are two significant factors that affect the silicate polymerization, solvating effect on micelles formation, and MCM-41 mesostructure formation. In view of that, this study investigates recycling of surfactant template ions in extract solution in Mobil Crystalline Material 41 (MCM-41) synthesis. Effect of the ethanol concentrations in the solution gel and the types of ion exchange agents on the yield of MCM-41 material and its surface morphology were studied. Hexadecyltrimethylammonium bromide was used as template for MCM-41 synthesis using tetraethylorthosilicate (TEOS) as silica reagent with ethanol-water mixture as solvent at different ethanol concentrations. Template ions of synthesis gel was exchanged with an ion exchange agent (i.e., 1-butyl-3-methylimidazolium chloride or ammonium nitrate) before it is extracted using synthesis solution. After extraction, the extracting solution was added with TEOS, used for second synthesis cycle and the process continued in an extraction. The template ions in the extract solution were further recycled up to eight synthesis cycles. Yield of calcined materials significantly influenced by ethanol solvent concentrations and however did not vary with various ion exchange agents. Nitrogen adsorption isotherms showed that the calcined materials exhibit MCM-41 characteristics with surface areas ranging from 600 – 1000 m2/g. It is possible to recycle and reuse the surfactant template for several subsequent times of preparing MCM-41 if the ethanol concentration in the solution gel controlled continuously.